178k views
4 votes
5x squared plus 13x-6=0​

User Sherida
by
5.4k points

2 Answers

3 votes

Explanation:

The easiest way to solve this (in my opinion) is to use the Pythagorean theorem
(-b+-√(b^2-4(a)(c)) )/(2a)

In this case, 5 is a, with the highest power, 13 is b, with the second highest power, and -6 is c, with a 0 power.

Or, looking at this equation
ax^2+bx+c we can gain that knowledge as well.

So let's plug these values in and solve!


(-b+-√(b^2-4(a)(c)) )/(2a) = (-13+-√(13^2-4(5)(-6)) )/(2(5))\\=(-13+-√(169+120) )/(10)=(-13+-√(289) )/(10)=(-13+-17 )/(10)

Now we simplify this into two different answers, one when we add, and one when we subtract:


add:(-13+17 )/(10)=(4)/(10)=(2)/(5)\\subtract:(-13-17 )/(10)=(-30 )/(10)=-3

So, assuming the question asked to solve for x (which I'm assuming it did), our answers are x = -3 and
(2)/(5)

Answer:

x = -3

x =
(2)/(5)

User Kevin Van Mierlo
by
5.3k points
5 votes
Use the quadratic equation: you get values of x=2/5 and x=-3
User Otero
by
6.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.